Draft Annual Plan 1972-73 Part I Government of Assam - Planning Commission (Planning Commission, 1972)
Assam is a land-locked State surrounded by the foreign territories of Burma and East Pakistan. It is situated very near to Tibet and China and has a common border with West Bengal, Nagaland, Tripura and Manipur. Geographically and from the point of view of communications with the rest of the country, Assam forms the care of the entire North-Eastern part of the country comprising Assam, Nagaland, North East Frontier ' Agency area, Manipur and Tripura. All lines of communications to these areas pass through Assam.
Government of Assam, Planning and Development Department